Adaptation Atlas Notebook: Understand heat stress on producers / Comprendre le stress thermique sur les producteurs - Steward, Peter; Youngberg, Brayden; Mehrabi, Zia; Muller, Lolita; Naia, Ormaza Zulueta; Rosenstock, Todd (2025)
This notebook analyzes how rising temperatures will affect agricultural producers across Africa by quantifying exposure to heat stress under current and future climate scenarios. It combines hourly climate projections with population and crop value data to estimate how many people and how much agricultural production are vulnerable at different heat thresholds. Users can explore impacts by hazard type, climate scenario, and time horizon to understand when and where heat stress will intensify. By translating complex climate data into accessible metrics, the notebook supports planning for heat-resilient farming systems, labor safety, and adaptation investments.